2004
DOI: 10.1073/pnas.0405065101
|View full text |Cite
|
Sign up to set email alerts
|

Regional glucose metabolism and glutamatergic neurotransmission in rat brainin vivo

Abstract: , and is indicative of a glutamate (Glu)͞glutamine (Gln) neurotransmitter cycling flux between glutamatergic neurons and surrounding astroglia. Although 13 C NMR spectroscopy offers a high spectral resolution (1), it suffers from an inherently low sensitivity, thereby limiting the detection to relatively large volumes. As an alternative to direct 13 C NMR spectroscopy, the protons bound to 13 C atoms can be detected by proton-observed, carbon-edited 1 H-[ C]Glx (Glx ϭ Glu ϩ Gln) is measured in volumes that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 42 publications
6
109
0
1
Order By: Relevance
“…Although the model currently allows the use of [1,[6][7][8][9][10][11][12][13] C 2 ]glucose only as enriched substrate, it can be extended to simultaneously analyze mixtures of substrates with appropriately different labeling patterns. This will help determine the extent to which different substrates are used in different compartments of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the model currently allows the use of [1,[6][7][8][9][10][11][12][13] C 2 ]glucose only as enriched substrate, it can be extended to simultaneously analyze mixtures of substrates with appropriately different labeling patterns. This will help determine the extent to which different substrates are used in different compartments of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In this study common assumptions involving the metabolism involved are those found in Figure 1 and outlined in the Materials and Methods section. All flux and substrate enrichment parameters were free parameters, determined only by fitting to the measured data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase the sensitivity, indirect detection of 13 C through the more sensitive 1 H nuclei is an alternative, albeit at the expense of a lower spectral resolution, such as the partial separation of labeling in Glu and Gln (23,25), which limits the achievable dynamic information and the reliability of the two-compartment metabolic modeling (20). For instance, Pfeuffer et al (23) proposed a modified stimulated echo acquisition mode localization for performing adiabatic carbon editing and decoupling, and demonstrated the measurement of GluC4 and GlnC4 time courses with glucose infusion at 9.4 T. A proton-observed carbon-edited NMR sequence (7) based on three-dimensional image-selected in vivo spectroscopy localization was performed with glucose infusion at 7 T in rat brain, and the reported time courses were limited to GluC4, GlnC4, and GluC3 þ GlnC3 (27).…”
mentioning
confidence: 99%